CRIMINAL LIABILITY ANALYSIS OF FORGERY OF ANTIGEN RAPID TEST LETTERS AT BAKAUHENI PORT - Andi Kristianto; Indah Satria (Law Faculty of Universitas Bandar Lampung, 2022)
The Criminal Act of Forgery of Letters is a criminal act whose implications have an impact on the truth and trust of people. The perpetrator uses a fake letter aimed at obtaining benefits for himself and for his actions it can harm others both losses of an individual nature and losses that have a broad impact on the act itself. The research methods used in this writing are normative juridical, and empirical approaches. The data used are secondary data and primary data. Data analysis uses descriptive analysis. Factors causing the perpetrator to commit a criminal act of forgery of a rapid antigen test letter in Case Number: 384/Pid.B/2021/PN. Kla is the Intention of the Perpetrator, the Factor of Low Education, the Factor of Economic Needs, and the Factor of Low Morals and Religious Knowledge. Liability of Criminal Offenders of forgery of rapid antigen test letters in Decision No. 384/Pid.B/2021/PN. Kla is charged with article 14 paragraph (1) of law of the Republic of Indonesia Number 14 of 1984 concerning Infectious Disease Outbreaks Jo Article 55 paragraph (1) 1 of the Criminal Code. The people of South Lampung Regency should support efforts to overcome the infectious disease outbreak carried out by the South Lampung Police So that Covid-19 in the South Lampung area can be overcome to the maximum. The Public Prosecutor should be careful and careful in compiling the indictment letter, so that the indictment letter can be used the basis for the judge to impose or not impose a sentence on the offender who is facing trial.